EDUCATION TOWARDS UNDERSTANDING AND AWARENESS OF HIBAH IN ESTATE PLANNING MANAGEMENT: A STUDY AMONG UITM STAFF - Che Norzila Sulong; Anis Natasya Binti Azizan; Azarudin Awang; Ahmad Faizal Ramly; Muhammad Hamdan Syafieq Ahmad (Journal of Islamic, Social, Economics and Development, 2024)
Unclaimed property left behind when the owner dies is a common phenomenon these days. One of Islam's methods for managing inheritance that is not frequently used by Muslims in this nation is the hibah. Due to a lack of information and the fact that they do not really disclose how hibah is used, the majority of Malaysian Muslims do not comprehend the notion of hibah. Additionally, individuals encounter challenges and need to seek advice to manage their property because institutions that provide estate management planning do not disclose their hibah practices. Numerous organisations still today offer hibah and other assistance for estate management planning. The objectives of the study are to know the level of understanding of the importance of hibah in estate management planning among UiTM staffs. Secondly, to look awareness of the importance of hibah in estate management planning among UiTM staffs. To achieve its goals, this study relies on quantitative techniques and uses a questionnaire survey to collect data. Further, the questionnaire was analyzed using SPSS 25 software by looking at the percentage, mean, standard deviation and T-test. The results of the study found that the level of understanding and awareness of UiTM lecturers about hibah in property management is high. Researchers also suggest that other researchers develop their research aspects more widely, not only at the level of a UiTM but also at the level of comparison according to the UiTM of other universities.